DOP53 Community types of the human gut virome are associated with endoscopic outcome in UC patients. (30th January 2023) - Jansen, D; Falony, G; Vieira-Silva, S; Simsek, C; Marcelis, T; Machiels, K; Caenepeel, C; Raes, J; Severine, V; Matthijnssens, J
Abstract: Background: Inflammatory bowel diseases (IBD) are a group of chronic inflammatory diseases of the gut. The pathophysiology is unknown; however, it is thought to result from an inappropriate immune reaction to the commensal gut microbiota. Community-typing is a common practice in bacteriome analysis allowing for the stratification of individuals based on their gut microbiome (eg., 'enterotyping'). A viral counterpart of these enterotypes might allow stratification of individuals based on their gut virome. The aim of the present study is to investigate the existence of such viral community types and assess the impact of therapeutic outcome (and other covariates) on the gut virome in IBD patients. Methods: Fecal samples were selected from 181 patients undergoing immunomodulatory therapy, and a baseline (pre-intervention) and a primary endpoint (post-intervention) have been collected for each patient. Viral metagenomics and deep sequencing were performed following viral enrichment with the NetoVIR protocol. Redundancy analysis and Dirichlet Multinomial Mixtures were applied to determine covariates of the virome composition and to condense the gut virota into viral community types, respectively. Results: IBD patients were stratified based on unsupervised machine learning into two viral community types. Community type CA showed a low α-diversity and a high relative abundance of Caudoviricetes [non-CrAss] phages and was associated to the dysbiotic Bact2-enterotype. Community type CrM showed a high α-diversity and a high relative abundance of Caudoviricetes [Cr Ass] and Malgrandaviricetes phages. The gut virome variation was explained by several factors: patients' individuality (75.8%), disease location (1.4%), age (0.5%) and faecal moisture (0.3%), with diagnosis not showing a non-redundant effect. Despite our expectations the choice of biological therapy did not show an association with the virome variation. During post-interventional analysis, endoscopic outcome (0.5%) was associated to gut virome variation as well. Remitting UC, but not CD, patients revealed a high percentage of community type CrM, a high Shannon diversity and a low phage lysogenic potential. Conversely, non-remitting UC, but not CD, patients revealed a high percentage of community type CA, a low Shannon diversity and a high lysogenic potential. Conclusion: These findings suggest that viral community-typing allows for stratification of IBD patients based on their gut virome composition and might be a valuable tool to better understand IBD subtypes or as a potential future biomarker.